ANALISIS IMPLEMENTASI MULTIMEDIA INTERAKTIF TERHADAP MOTIVASI BELAJAR SISWA BERDASARKAN SELF-DETERMINATION THEORY DALAM PEMBELAJARAN BAHASA INGGRIS - Awaluddin, Muhammad; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of interactive multimedia on students’ learning motivation based on Self-Determination Theory in English learning at class XI MAN 2 Makassar City. This research employed a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, involving an English teacher and students of class XI MAN 2 Makassar City as the research subjects. The findings showed that the use of interactive multimedia, such as videos, animations, and digital applications, increased students’ attention, enthusiasm, and engagement in learning. Based on the perspective of Self-Determination Theory, students’ learning motivation developed in three main aspects: autonomy, competence, and relatedness. However, students’ participation and engagement were not evenly distributed, and classroom interaction tended to be one-way. Therefore, more participatory and student-centered learning strategies are needed to optimize the use of interactive multimedia in improving students’ learning motivation.